Analysis of the Content of Da'wah Messages in the "Sparkling Ramadan 1446 H" Ngaji Ngabuburit Program at Al Akbar National Mosque Surabaya - Chillyness, Altruis Bizurai; Yuli Hermawati; Akhmad Ainur Roziqin; Abiidah Nafisa Fiqriyah; Saifi Atoillah; Shinta Purnama Sari (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
This study aims to analyze the content of Islamic preaching messages delivered in the “Ngaji Ngabuburit Sparkling Ramadan 1446 H” program held at the National Al Akbar Mosque, Surabaya. The research specifically focuses on four preachers: Ustadz Nawawi, Dr. KH. Syukron Djazilan Badri, M.Pd.I, Ustadz HM Sholeh Drehem, Lc., M.Ag, and DR. KH. M. Sudjak, M.Ag, each of whom presented themes relevant to spiritual development and social awareness. This qualitative study employed observation and in-depth interviews during the pre-survey stage to explore the context and audience engagement within the program. The collected data was then analyzed using Ferdinand de Saussure's semiotic theory and the theory of preacher competence from the Usul ad-Da'wah framework by Abdul Karim Zaidan. The findings indicate that the effectiveness of Islamic preaching is significantly influenced not only by the substance of the message but also by the preacher's ability to deliver it in a relatable, contextual, and emotionally engaging manner. Each preacher employed different rhetorical and linguistic strategies to align their message with the needs of contemporary audiences, particularly Generation Z. Themes such as personal piety, social responsibility, gratitude, and the pursuit of true happiness were emphasized and presented in ways that fostered emotional resonance and reflective understanding among the congregation. The study concludes that effective Islamic preaching must be audience-oriented, contextually grounded, and spiritually transformative.